Sport expertise in perception–action coupling revealed in a visuomotor tracking task. Issue 10 (26th November 2017) - Mallek, Maroua; Benguigui, Nicolas; Dicks, Matt; Thouvarecq, Regis
Abstract: We compared the visuomotor coordination of tennis players with different levels of expertise (Super-Experts, Experts and Non-Experts) in a visuomotor tracking (VMT) task. Participants were asked to track a moving target which could rebound on the sides of a 2D screen. Results indicated that the VMT task allowed the discrimination of expertise. Multiple regression analysis revealed that performance could be explained by the temporal adaptation of participants to rebounds and the number of movement adaptations. Compared to Non-Experts, the Experts had a shorter perturbation time with higher adaptation and regulation. This corresponds to a better perception–action coupling and the predominant use of a prospective control process. Results also indicate that perception–action coupling capacities are transferable to virtual tasks, and allow us to reveal processes of visuomotor coordination that differentiate experts and novices.